Rapid elemental composition analysis of spinach samples employing wavelength dispersive X-ray fluorescence spectroscopy. Issue 4 (21st April 2021) - Kainth, Harpreet Singh; Singh, Tejbir; Khandelwal, Deeksha; Singh, Gurjeet; Puri, Sanjiv
Abstract: The increasing demand to carry out nondestructive analysis with minimal sample preparation for the detection of chlorine element in the spinach samples requires advanced analytical techniques with better energy resolution. The emergence of wavelength dispersive X-ray fluorescence instruments offers new chances for fast and inexpensive plant leaf analysis, both as laboratory and in-situ-based systems. Earlier efforts to use X-ray fluorescence analyses for various plant samples, especially spinach leaves, were limited by the large background caused by scattering of the primary X-ray source which has been overcome by using the commercial wavelength dispersive technique. It is a potential influential research tool for the study of trace elemental composition analysis under different analytical parameters and simple sample preparation protocols. In the present work, the chlorine content ∼0.8% has been measured in the spinach leaf standard reference material (SRM 1570a) from the National Institute of Standards and Technology, USA by using the wavelength dispersive X-ray fluorescence technique employing a fundamental parameter approach. Keeping in view the importance of the knowledge about the chlorine content in plant leaf samples and the reliability of the methodology used in the present work to determine chlorine content, it is recommended that the present measured chlorin.e concentration be included in the datasheet of certified values by the National Institute of Standards and Technology, the USA for effective use of this standard reference material.